Effectiveness of Periarticular Infiltration of the Knee during Total Knee Arthroplasty for Postoperative Pain Management - Mishra , Bibhuti Nath; Chowdhury , Joydeep Banerjee; Raman , Rajeev; Chakraborty , Dipmalya; Karmakar , Tanmoy (Europasian Journal of Medical Sciences, 2021)
Background: Different treatment regimens of analgesia, nerve blocks and epidurals are used for pain relief in Total Knee Arthroplasty (TKA). Local infiltration analgesia (LIA) is one of the modalities in which a cocktail combination of different medicines is infiltrated locally into the capsule, surrounding tissues or intraarticular joint space. This study aims to analyze the effectiveness of periarticular injection of combination drugs (Bupivacaine, Ketorolac and Morphine) during TKA for postoperative pain management. Methods: A Total of 150 patients who underwent primary unilateral TKA were randomly categorized into 2 groups (75 each). Group A (control group) didn’t receive intraoperative periarticular injection but Group-B received the intraoperative injection of combined local analgesics and anaesthetics (Bupivacaine, Ketorolac and Morphine). Pain following surgery at 0, 1, and 2 postoperative days were recorded with visual analogue scale (VAS) whereas the Knee Society Score was used to evaluate the pain and function pre-operative and 3 months post-operative. Statistical analysis was done using SPSS software. Results: Patients receiving periarticular infiltration of combination drugs intraoperatively had lower VAS for postoperative pain (p < 0.001), and this group also showed reduced need for analgesia postoperatively. Conclusions: Periarticular infiltration of the knee during Total Knee Arthroplasty is effective in the management of postoperative pain DOI: https://doi.org/10.46405/ejms.v3i2.341